2016
DOI: 10.1007/s13595-016-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Using joint multivariate analyses of leaf morphology and molecular-genetic markers for taxon identification in three hybridizing European white oak species (Quercus spp.)

Abstract: & Key message We show that joint multivariate analyses of leaf morphological characters and molecular-genetic markers improve the taxonomic assignment in hybridizing European white oaks. However, model-based approaches using genetic data alone represent straightforward alternatives to laborious, detailed morphological assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 41 publications
(52 reference statements)
2
42
1
1
Order By: Relevance
“…In the case of oaks, the recently proposed validated multiplexes of microsatellites were used mostly to study mating patterns (Lagache et al, 2014), interspecific hybridization processes (Lander et al, 2013) or species identification (Neophytou, 2013;Rellstab et al, 2016) rather than genetic diversity (Curtu et al, 2015;Moracho et al, 2016). Nevertheless, the levels of population genetic parameters found in our study were similar to those observed by other authors (Streiff et al, 1998;Cottrell et al, 2003;Curtu et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…In the case of oaks, the recently proposed validated multiplexes of microsatellites were used mostly to study mating patterns (Lagache et al, 2014), interspecific hybridization processes (Lander et al, 2013) or species identification (Neophytou, 2013;Rellstab et al, 2016) rather than genetic diversity (Curtu et al, 2015;Moracho et al, 2016). Nevertheless, the levels of population genetic parameters found in our study were similar to those observed by other authors (Streiff et al, 1998;Cottrell et al, 2003;Curtu et al, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Earlier phylogenetic reconstruction considering temperate white oaks were unable to resolve the relationship between our four species (Bellarosa et al ., ; Denk & Grimm, ; Hubert et al ., ). However, recent genetic survey conducted with genetic markers highlighted closer genetic relationships between Quercus pubescens and Q. petraea (Curtu et al ., ; Lepais et al ., ; Neophytou et al ., ; Rellstab et al ., ). These results were also confirmed by phenetic analysis based on leaf morphological features showing that Q. pubescens and Q. petraea share strong leaf morphological similarities in contrast to Q. pyrenaica and Q. robur (Viscosi et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…() as detailed in Rellstab et al . (). The nSSR data were used for species assignment (Rellstab et al .…”
Section: Methodsmentioning
confidence: 97%
“…The nSSR data were used for species assignment (Rellstab et al . ) and as population genetic basis for the EAA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation